Historical Development and Special Building Structures of In-earth Embedded Houses - Bozsaky, D. (Acta Technica Jaurinensis, 2015)
Earth houses have been traditional residential buildings for a long time and their three different types (in-hill house, cave dwelling and atrium house) were separated during the early history. Modern earth house architecture was born in the 1960s in the USA but spread only after the first oil price explosion in the 1970s. Earth-sheltered houses became popular nowadays because of their several benefits (environmentally friendly, economical, energy savings, landscape protection, fire protection). Unfortunately they have some disadvantages (negative prejudices, high building costs, special building constructions, complicated design and construction) this is why we can come across these houses very rarely. The well-designed orientation, insolation, ventilation, damp and thermal insulation is essential to have pleasant and comfortable atmosphere inside.